PENINGKATAN HASIL BELAJAR DALAM PEMBELAJARAN BIOLOGI MELALUI PENERAPAN STRATEGI SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) PADA SISWA KELAS XI IPA 2 SMA NEGERI 1 BANYUDONO TAHUN AJARAN 2011/2012 - Palupi, VA Vellariani Dewi; Santosa, Slamet; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? This research aimed for improving studentachievementin learning process on Biology by implementation of Survey, Question, Read, Recite, and Review (SQ3R) strategy of grade XI IPA 2 SMA Negeri 1 Banyudono academic years 2011 / 2012. This research is aclassroom action research that was included 2 cycles of action. Each cycles consisting of 4 phase which areplanning, action, observation, and reflection. The subjects of this research were students grade XI IPA 2 SMA Negeri 1 Banyudonoacademic years 2011 / 2012. Source of data derived from the questionnaire, observation, test and interview. Technical analysis of data was using descriptive analysis. Data validation was using methods triangulation. The results of this research showed that the implementation Survey, Question, Read, Recite, and Review (SQ3R) strategy could improve student achievement in learning process on Biology of grade XI IPA 2 SMA Negeri 1 Banyudonoacademic years 2011 / 2012. The average percentage based on questionnaire student achievement of psychomotorindicators was 75,49% forCycle Iand 80,02% forCycle II(worked up 4,53%). The average percentage based on questionnaire student achievement of affective indicators was 69,48% forCycle Iand 78,09% forCycle II (worked up 8,61%). The average percentage based on observation student achievement of psychomotor indicators for Cycle I was 57,81% and 67,60% forCycle II (worked up 9,79%). The average percentage based on observation student achievement of affective indicators for Cycle I was 55,35% and 63,76% forCycle II (worked up 8,41%). The average percentage student achievement of cognitivebased on evaluation test for Cycle I was 74,84and 85,63for Cycle II (worked up 10,79).Based on the result could be conclude that implementation of Survey, Question, Read, Recite, and Review (SQ3R) strategy had improvedstudent achievement in learning process on Biologyof grade XI IPA 2 SMA Negeri 1 Banyudono. Keywords: Survey, Question, Read, Recite, and Review (SQ3R), Psychomotor, Affective, Cognitive,and Students Achievement